PENENTUAN KOMPONEN KRITIS UNTUK MENGOPTIMALKAN KEANDALAN MESIN CETAK - Ag Eko Susetyo; Eko Nurhardianto (Universitas Sarjanawiyata Tamansiswa, 2019)
Equipment maintenance activities are very important in the operation of a system or equipment in the industry. With the maintenance strategy and methods that can affect the occurrence of damage resulting in equipment can operate in the long term. The methods used are Reliability Centered Maintenance (RCM) data required are working hours data, corrective time data, Supply Delay Time (SDT) and Administrative Delay Time (ADT) data, and prevetive maintenance data. To determine whether the data obtained suadah match, then used the exponential distribution, from the form of the data then it can be found treatment. From the exponential distribution will get the value of cumulative function, machine reliability, Maen Time Batwen Failure (MTBF), Mean Time Battery Maintenance (MTBM), machine readiness time (availability) for each machine. There are two critical components: laker / bearing and felt print. From the data processing obtained reliability of printing machine unit 1 99.9%, machine unit 2 92.52%, unit 3 91.85% machine. for that we need preventive maintenance. In addition to the reliability also obtained MTBM as a schedule of preventive maintenance on mesn print unit 1 66.105, unit 2 93.037 machine, machine unit 3 106,893 hours once.Keywords: Reliability, RCM, Preventive Maintenance